3‐D printed texture spoons for food flavor and satiety. Issue 3 (18th February 2021) - Smith, Molly I.; Dando, Robin
Abstract: Foods are perceived when they are eaten through input from the senses, however our sensory modalities (taste, smell, touch, sight, and hearing) do not operate entirely independently. The objective of this study was to test how sensory input from texture, provided extrinsically to the food, impacts taste, and underlying feelings of satiety from food consumption. In order to perturb the perceived texture of a sample without altering the food itself, a set of six 3‐D printed spoons, including a smooth‐textured control, was created. A total of 106 panelists tested samples of yogurt in a consumer test of liking, perceived flavor intensity, and ideal consumption amount. Although no changes in the sample's flavor were reported by the panel, participants displayed small but significant differences in how much they perceived they would eat using the texture spoons, without a significant reduction in liking of the yogurt when consumed from either of the spoons versus control. From these results, a second test ( n  = 65) compared ad libitum consumption of yogurt on 2 consecutive days, using an un‐textured spoon versus one of the textured 3‐D printed spoons. Although slightly less yogurt was consumed from the textured spoons, differences were not statistically significant versus control. Practical Applications: There is growing interest in the food industry in 3‐D printing. Here, we present 3‐D printed spoons with varying textures, aimed at influencing a product's flavor or satiating properties. Panelists rated their ideal portion sizes to be lower with the spoons, suggesting they may have some utility in portion control.